High-temperature oxidation behavior of additively manufactured IN625: Effect of microstructure and grain size. (15th August 2022) - Chyrkin, Anton; Gunduz, Kerem O.; Fedorova, Irina; Sattari, Mohammad; Visibile, Alberto; Halvarsson, Mats; Froitzheim, Jan; Stiller, Krystyna
Abstract: High-temperature oxidation of additively manufactured (AM) Ni-base alloy IN625 has been studied in air and Ar-5%H2 -3%H2 O at 900–1000 °C. AM material is found to oxidize faster than the conventionally manufactured (CM) IN625 due to severe intergranular oxidation observed in the former. The AM IN625 was heat treated at 1100–1250 °C and hot rolled at 980 °C in order to modify the AM microstructure, primarily grain size, and analyze its role in alloy oxidation behavior. Grain size is shown to affect overall oxidation kinetics but not the intergranular oxidation morphology. Highlights: Additively manufactured IN625 oxidizes faster than its conventional counterpart. Higher oxidation kinetics for AM is due to severe intergranular oxidation. Excessive mass gain for AM IN625 correlates well with GB density. Microstructural manipulation does not affect intergranular oxidation morphology.